2019
DOI: 10.1016/j.athoracsur.2018.07.080
|View full text |Cite
|
Sign up to set email alerts
|

Intra-Extracardiac Versus Extracardiac Fontan Modifications: Comparison of Early Outcomes

Abstract: Background. The intra-extracardiac (IE) Fontan modification has advantages over the lateral tunnel modification. A direct comparison of IE to the extracardiac (EC) modification so far has not been done. This study compared IE to EC Fontan with respect to early postoperative outcomes.Methods. We retrospectively compared outcomes of the Fontan operation using the IE or EC conduit modification between January 2012 and December 2016. IE and EC groups were compared using univariate and multivariable regression anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 13 publications
0
7
0
Order By: Relevance
“…It was thought that early extubation was associated with shorter drainage time and hospital stay (12). There were also articles reporting that IEC Fontan procedure was related with shorter drainage period than the EC Fontan procedure (13). In our study, absence of a standardized treatment protocol wasdetermined as a risk factor for prolonged drainage.…”
Section: Commentmentioning
confidence: 51%
“…It was thought that early extubation was associated with shorter drainage time and hospital stay (12). There were also articles reporting that IEC Fontan procedure was related with shorter drainage period than the EC Fontan procedure (13). In our study, absence of a standardized treatment protocol wasdetermined as a risk factor for prolonged drainage.…”
Section: Commentmentioning
confidence: 51%
“…14 It has also been reported that the drainage period was shorter for the IEC Fontan procedure than the EC Fontan procedure. 15 In our study, the absence of a standardized treatment protocol was determined as a risk factor for prolonged drainage.…”
Section: Discussionmentioning
confidence: 95%
“…In the era of LT and ECF, the spontaneous closure of surgically created fenestrations could be as high as 19% ( 14). Sinha et al reported that only 66% of fenestrations were patent at the time of discharge in ECF patients, whereas this ratio was 95% in IECF patients (22). In a catheter-based analysis in 35 patients, Hirofumi and colleagues reported that persistent fenestration in Fontan circulation suppresses heart rate and CVP, which secures preload reserve without compromising systemic oxygen delivery (23).…”
Section: Discussionmentioning
confidence: 99%